2018
DOI: 10.13102/sociobiology.v65i1.1838
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Contribution of Termites to Mass Loss of Dead Wood among Three Tree Species during 23 Months in a Lowland Tropical Rainforest

Abstract: This study investigated the contribution of termites to mass loss of dead wood (Macaranga bancana, Elateriospermum tapos, and Dillenia beccariana) in a lowland tropical rainforest, Brunei Darussalam. Mesh bag method was used to exclude termites, and the mass remaining was monitored after 3, 7, 13, and 23 months. C/N ratio of the samples was analyzed after 13 and 23 months. Initial wood density was 0.63, 0.92, and 1.02 g/cm3 for M. bancana, E. tapos, and D. beccariana, respectively, and the termite contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Deadwoods are traditionally considered to require an extended period of the decomposition process 1 . Previous studies have also reported either an increase 26 or a decrease 40 in the contribution of invertebrates to deadwood decomposition with the time frame. Hence, further monitoring should be followed to ensure if the divergence in the regional variation between pine and oak deadwood decomposition persists in the long term.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Deadwoods are traditionally considered to require an extended period of the decomposition process 1 . Previous studies have also reported either an increase 26 or a decrease 40 in the contribution of invertebrates to deadwood decomposition with the time frame. Hence, further monitoring should be followed to ensure if the divergence in the regional variation between pine and oak deadwood decomposition persists in the long term.…”
Section: Discussionmentioning
confidence: 87%
“…This pattern implies that inconsistent sensitivity to decomposer invertebrates possibly led to the different regional variations between pine and oak deadwoods. In fact, the differences in feeding preference are not uncommon in other termite studies 12 , 40 , 41 , and termites’ feeding preferences could intensify the effect of tissue density and recalcitrant compound content on wood decomposition rate 23 . Furthermore, the detected subterranean termite species, R. speratus kyushuensis is known to prefer P. densiflora than broadleaf tree species as a feeding source because of the difference in wood density and recalcitrant chemical content 28 .…”
Section: Discussionmentioning
confidence: 96%